Investigation of Short-term Variations in Term Breast Milk Composition during Repeated Breast Expression Sessions. (May 2013) - Khan, Sadaf; Prime, Danielle K.; Hepworth, Anna R.; Lai, Ching Tat; Trengove, Naomi J.; Hartmann, Peter E.
Background: Breast milk composition can be affected by several factors, and it can exhibit short-term (weekly) variations. Investigating variations in breast milk composition is important to accurately estimate nutrient requirements of the infant. Objective: To investigate short-term changes in breast milk composition between left and right breasts, over a 3-week period within the first 6 months of lactation. Methods: The left and right breasts of the mothers of healthy, term infants (n = 23) were simultaneously expressed with an electric breast pump for 15 minutes, on 3 occasions within 3 weeks. Milk samples (5 mL) were collected from the total expression volume of each breast at each session. The macronutrient contents, total solids, and energy content were determined using a mid-infrared human milk analyzer. Mothers (n = 17) measured their 24-hour milk production, and the average 24-hour fat contents were also determined. Results: Over the 3 weekly sessions, no significant changes were found in macronutrient contents. On average, total solids ( P = .04) and energy ( P = .04) decreased by week 3 of follow-up sessions from 14 to 13 g/100 mL and from 82 to 76 Kcal/100 mL, respectively; however, these changes became insignificant when expression volume was taken into account. The macronutrient concentration was similar for the left and right breasts; however, milk composition varied markedly between mothers. Furthermore, average 24-hour fat content was significantly lower than the mean fat content from a single expression session ( P < .01). Conclusion: Our findings highlight that when determining the nutritional adequacy of a mother's milk, assuming an average concentration requires caution. The study findings illustrate the importance of using average 24-hour fat content of milk to obtain representative measures of infant energy intake.